PSIKOEDUKASI PENGAMALAN MAKNA PERSATUAN BAGI WARGA CENGKARENG - Tumanggor, Raja Oloan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
In anticipation of the 2024 political year, the atmosphere of discussion in society is starting to heat up. They discussed the presidential candidates who will compete in the upcoming 2024 presidential election. Everyone supports the candidate they support and criticizes other candidates who are deemed not to be defending the interests of the people. Conditions of heated discussions between citizens with different political views can often cause citizens to become divided. The condition of society, which is already diverse in terms of ethnicity, culture, religion and economic conditions, will accelerate the collapse of the unity order among citizens as the legislative and presidential elections approach in 2024. Residents in RT 10, Cengkareng Timur Subdistrict, West Jakarta are no exception, also experiencing the potential for division as the upcoming legislative and presidential elections approach. Therefore, the PKM, which was attended by 20 participants, was carried out in the form of psychoeducation to practice the meaning of unity which was considered quite important and relevant for the residents of East Cengkareng in order to reduce the potential for division and division among the residents of East Cengkareng. With the method of presentation, question and answer and sharing experiences, this PKM activity aims to increase understanding and awareness of East Cengkareng residents regarding the importance of maintaining unity even though they have different political views, ethnic backgrounds, culture, religion and beliefs ABSTRAK Dalam rangka menyongsong tahun politik 2024 suasana diskusi di tengah masyarakat sudah mulai tampak memanas. Mereka membahas kandidat presiden yang bakal bertarung pada pemilu presiden 2024 yang akan datang. Setiap orang menjagokan kandidat yang didukungnya dan mencela kandidat lain yang dinilai kurang membela kepentingan rakyat. Kondisi diskusi panas antar warga yang berbeda haluan politiknya tidak jarang dapat membuat warga menjadi terpecah belah. Kondisi masyarakat yang memang sudah beragam baik dari segi suku, budaya, agama dan kondisi ekonomi akan mempercepat runtuhnya tatanan persatuan di antara warga pada saat menjelang pemilu legislatif dan presiden pada 2024 mendatang. Tidak terkecuali warga di RT 10 Kelurahan Cengkareng Timur, Jakarta Barat juga mengalami potensi keterpecahan pada saat menjelang pemilu legislatif dan presiden yang akan datang. Oleh karena itu PKM yang diikuti oleh 20 peserta ini dilaksanakan dalam bentuk psikoedukasi pengamalan makna persatuan dirasa cukup penting dan relevan dilakukan bagai warga Cengkareng Timur guna meredam potensi terjadinya keterpecahan dan sekat-sekat di tengah warga Cengkareng Timur. Dengan metode presentasi, tanya jawab dan sharing pengalaman kegiatan PKM ini bertujuan untuk meningkatkan pemahaman dan kesadaran warga Cengkareng Timur akan pentingnya memelihara persatuan kendatipun mereka memiliki haluan politik, latar belakang suku, budaya, agama dan keyakinan yang berbeda-beda